Retroperitoneal tumor: giant cavernous hemangioma – case presentation and literature review - Zielinski, Jacek; Haponiuk, Ireneusz; Jaworski, Radoslaw; Peksa, Rafal; Irga-Jaworska, Ninela; Jaskiewicz, Janusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Retroperitoneal hemangiomas are very rare. This paper presents the case of a 71-year-old female patient with giant cavernous hemangioma of the retroperitoneum who underwent surgical treatment for abdominal pain and left lower limb edema. Interventional staged treatment with percutaneous transcatheter arterial embolization prior to surgery was considered. Radical resection of the tumor was performed, which caused the symptoms to abate. Additionally a literature review of cases involving cavernous hemangioma in the retroperitoneal space is presented. No description of retroperitoneal cavernous hemangioma originating from the bowel was found in the analyzed reports.